Development of Simulation Model for Transradial Catheterization Practice for Physicians - Julthongpipat K. (2023)
Objective: This study tested different types of silicone rubber material to assess the most durable with properties that best simulated the human skin and vascular. The optimal materials were used to produce a transradial catheterization simulation model to train medical practitioners and tested the improvement of the training with a medical simulation model. Materials and Methods: Three types of silicone rubber were tested for their suitability as artificial skin and vascular for transradial catheterization simulation model. Eighteen fellowship physicians assessed the simulator’s operational effectiveness and recorded their satisfaction with the training. Results: Silicone rubbers were tested for realism and capability for repetitive training. Silicone rubber RTV-01 was the most durable for simulating the artificial skin, while silicone rubber RTV-03 was the most durable for simulating the artificial vascular with statistically significant results recorded by Kaplan-Meier analysis (P < 0.1). Satisfaction assessment results of the 18 participants using a Likert scale (5 points) returned total average scores of model’s efficacies as 4.41 and total average scores of model’s usefulness as 4.59. Conclusion: The materials were used for transradial catheterization simulation to enhance fellowship trainees’ learning efficiency through practice. The fellowship trainees became familiar with the equipment, gained a higher completion rate, and increased confidence in treatment planning